MANDIBULAR FLEXURE - A REASON FOR CHRONIC PAIN SYNDROME IN EDENTULOUS PATIENT RESTORED WITH FIXED ZRO2 CONSTRUCTION OVER IMPLANTS, INSERTED IN NATURAL BONE AND BONE GRAFT AREA. Case report - Metodi Abadzhiev; Georgi Todorov; Konstantin Kamberov (Peytchinski Publishing, 2017)
Introduction: The experience of more than fifty years of implantology practice has led to several conclusions or suggestions that led to scientific investigations. It is known that as every other matter the bone has a certain elasticity (Young's modulus). The human mandible has its Young modulus and flexes during masticatory action. This flexure is limited when the entire natural dentition is splinted with metal-ceramic or ZrO2 prosthetic construction because the elasticity of metal and ZrO2 is very low. What happens with the mandible flexure strain when there is edentulous jaw rehabilitated with eight implants that does not have periodontium and they are splinted together with rigid prosthetic construction is still not exactly clear. Even far uncertain if implants are inserted in different hard tissues - partially natural bone and partially in guided bone regeneration area with unresorbable xenograft material. This is the reason for this case report in a patient with rigid construction over implants and occurrence of unilateral chronic pain syndrome. Aim: The purpose of this case report is to inform for a chronic unilateral pain syndrome in patient rehabilitated with fixed prosthetic construction made by zirconium dioxide over eight dental implants (TS III SA Fixture Osstem Implants) distributed over the entire mandible (4 implants in the frontal region and one on each side in the premolar region and one on each side in molar region). Methods and Materials: Analysis of the literature for studies of the distribution of stress on the mandible during masticatory function as well as Young's modulus in different parts of the mandible. Experimental study by using Cone beam computer tomography analysis of mandible and mathematical analysis made on the finite element method. Conclusion: Clinical data, x-rays and CT, mathematical analysis made on the finite element method, show mandibular elasticity could be cause of pain syndrome in case of edentulous mandible case with rigid fixed prosthetic construction over dental implants inserted in different kind of bone structure.